The Influence of Perceived Value and Product Quality on Purchase Intention with Brand Trust as a Mediating Variable: A Study on Rucas Limited Edition Products - Multi Aldi Nugroho; Heriyadi Heriyadi; Daud Ilzar; Juniwati Juniwati; Pebrianti Wenny (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the digital era and amidst increasingly intense competition in the fashion industry, local brands are required to continuously innovate to remain relevant and appealing to consumers. RUCAS, as a local Indonesian streetwear brand, is known for its limited edition marketing strategy that successfully creates a sense of exclusivity and enhances product appeal. This study aims to analyze the influence of perceived value and product quality on consumers’ purchase intention toward RUCAS limited edition products, as well as to examine the role of brand trust as a mediating variable. This study takes a quantitative approach, utilizing the Structural Equation Modeling (SEM) technique. Data were collected through questionnaires distributed to 200 respondents who had purchased or were familiar with RUCAS products. The results indicate that perceived value and product quality significantly influence both brand trust and purchase intention. Furthermore, brand trust is proven to mediate the relationship between perceived value and product quality with consumer purchase intention. These findings emphasize the importance of maintaining high product quality and creating strong perceived value to build trust and increase consumer purchase intention, particularly in the context of exclusivity-based marketing strategies such as those implemented by RUCAS.